How might a disorderly resolution of global imbalances affect global wealth? - Warnock, Francis E. (IMF working paper ;, 2006)
Partly reflecting structural advantages such a liquidity and strong investor protection, foreigners have built up extremely large positions in U.S. (as well as other dollar-denominated) financial assets. This paper describes the impact on global wealth of an unanticipated shock to U.S. financial markets. For every 10 percent decline in the dollar, U.S. equity markets, and U.S. bond markets, total wealth losses to foreigners could amount to about 5 percentage points of foreign GDP. Four stylized facts emerge: (i) foreign countries, particularly emerging markets, are more exposed to U.S. bonds than U.S. equities; (ii) U.S. exposure has increased for most countries; (iii) on average, U.S. asset holdings of developed countries and emerging markets (scaled by GDP) are very similar; and (iv) based on their reserve positions, wealth losses of emerging market governments could, on average, amount to about 2 3/4 percentage points of their GDP.